2016
DOI: 10.3765/amp.v3i0.3653
|View full text |Cite
|
Sign up to set email alerts
|

“Tense” /æ/ is still lax: A phonotactics study

Abstract: The production of the lax vowel /æ/ is widely studied as a sociolinguistic variable in American English, as several dialects differ in the allophonic distribution of lax and tense variants of the vowel. Using a forced-choice well-formedness judgment task, this paper tests whether the /æ/ used by Northern Cities Shift (NCS) speakers, which is described as a raised and tensed [ɛə] in all environments, is still represented as a lax vowel in speakers’ grammars. Participants who were native speakers of California E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is not, however, an indication that TRAP becomes phonologically recategorized as [+Peripheral] in the variety (see also Labov, 1994:505). Perceptual support for this claim comes from Duncan (2016), who tested the acceptability of [Vsk] and [Vsp] nonce words and found that for both California and TRAP-"tensing" Northern Cities Shift participants, TRAP -presented as low and front for California participants and raised and front for Northern Cities Shift participants-were judged equally as acceptable in [Vsk] and [Vsp] nonce words as DRESS and KIT, and, like DRESS and KIT, more acceptable than FACE or FLEECE. Duncan (2016:11) concluded that Northern Cities Shift TRAP is phonologically lax regardless of its phonetic characteristics.…”
Section: Phonological Motivationsmentioning
confidence: 99%
“…This is not, however, an indication that TRAP becomes phonologically recategorized as [+Peripheral] in the variety (see also Labov, 1994:505). Perceptual support for this claim comes from Duncan (2016), who tested the acceptability of [Vsk] and [Vsp] nonce words and found that for both California and TRAP-"tensing" Northern Cities Shift participants, TRAP -presented as low and front for California participants and raised and front for Northern Cities Shift participants-were judged equally as acceptable in [Vsk] and [Vsp] nonce words as DRESS and KIT, and, like DRESS and KIT, more acceptable than FACE or FLEECE. Duncan (2016:11) concluded that Northern Cities Shift TRAP is phonologically lax regardless of its phonetic characteristics.…”
Section: Phonological Motivationsmentioning
confidence: 99%